Risk Identification and Assessment Through Construction Project Lifecycle in UAE - Juem, Fayiz (2022)
A Master of Science thesis in Construction Management by Fayiz Juem entitled, “Risk Identification and Assessment Through Construction Project Lifecycle in UAE”, submitted in April 2022. Thesis advisor is Dr. Sameh El-Sayegh and thesis co-advisor is Dr. Abroon Qazi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).